ETIKA SOSIAL JAWA DALAM NOVEL IBU KARYA POERWADHIE ATMODIHARDJO - Serdaniar Ita Dhamina (JURNAL KONFIKS, 2019)
The purposes of this research is to describe: Javanese social ethics in the novel Ibu by Poerwadhie Atmodihardjo. This research is a qualitative descriptive research with content analysis method. The result of the analysis is Javanese social ethics in the novel Ibu by Poerwadhie Atmodihardjo are principle of harmony, principle of respect, etiquette, ethics in seeking justice, and profession ethics.